The Topu Waste Water Quality The Pondsand The Affect To Tarai, River - Julia Rastifa Dewi; Budijono Budijono; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbtrakThe research was conducted on November 2018 untill February 2019 in UD Dika Putra tofu industry. The research aimed to analyze the condition of tofu industry waste water, the efffectivenes of stabilization ponds in improving the waste water quality and the effects of discharged waste waste in tarai river. The method used in this research was survey method. Parameter measured were temperature, pH, BOD5, COD, TSS and NH3. Waste water quality varied from suhu 27-33 oC, pH 4-7, BOD5 4,8-132 mg/L, COD 1728-5568 mg/L, TSS 10-170 mg/L dan NH3 0,2-3,4 mg/L. Eventhough, the effectiveness value of the pons varied from suhu 3,2-15,6 %, pH 0-75 %, BOD 5 10,6-87,5 %, COD 0-58,6 %, TSS 9,1-85,3 %, NH3 2,6-331,9 %. Beside of that the Tarai River’s water quality varied from suhu 26-29 oC, pH 5-6, BOD5 4,8-76,8 mg/L, COD 578-3072 mg/L, TSS 10-85 mg/L dan NH3 0,1-1,65 mg/L. Generally, the treated tofu waste water that was not affect to the Tarai River’s quality Keywords: tofu industry, the effectiveness, Tarai River